Analysis of turbulence model effect on the position of the combustion zone in a swirling flow - Matvienko, Oleg V. (Proceedings of SPIE)
The influence of the turbulent combustion model on the position of the flame zone in a swirling flow is analyzed. Three models of turbulent combustion were analyzed: a model of volumetric combustion, a model of turbulent pulsations, and a model of vortex decay. The research results show that the data of the combustion model controlled by turbulent mixing are in the best agreement with the experimental data.